Ethical climate and culture of pediatric patient safety in a hospital specialty of southeast Mexico - Lopez Frias, Esmeralda; Vicente-Ruiz, María Asunción; De la Cruz García, Carmen (Horizonte Sanitario, 2019)
Objetive: To determine the relationship between the organizational ethical climate and the Safety Culture of the Patient in the nursing staff of the Regional Hospital of High Specialty of the Child “Dr. Rodolfo Nieto Padrón “.Materials and methods: Quantitative, descriptive, correlational and transversal study, the survey of Linda Olsón (1988) and the culture of patient safety, the questionnaire MOSPS (2011) used as instruments to measure the hospital ethics climate. The sample consisted of 168 nursing professionals.Results: The global index of hospital ethical climate of 56.29, nurses perceived a climate overall security of 8 (57.1%), on a scale of 0 to 10. Events reported in one year were 0 incidents in writing (88.7%). It was found that there is a positive and significant association (rs = .404; p = .000) between the ethical climate and the adverse events, as well as the ethical climate with safety (rs = .231; p = .003) and the hospital’s ethical climate and the perception of patient safety (rs = .636; p = .000).Conclusions: The perceived hospital ethical climate is oriented towards a positive and reliable environment in the collaborative work between professionals and patients, in contrast to the findings of distrust and subordination that are unfavorable for professional practice with other disciplines, the relationship with the chiefs and with the hospital. Keywords: Climate; ethics; culture; patient safety; pediatric hospital, nursing.